A Review on Strength Characteristics of Concrete Using Fly Ash and Steel Fiber under Alkaline Attack - Neelam Prasad Choudhary; Rakesh Sakale; Hirendra Pratap Singh (International Journal of Scientific Research in Civil Engineering, 2025)
This review paper investigates the experimental enhancement of concrete strength through the incorporation of industrial waste materials—specifically fly ash and steel fibers—under alkaline environmental exposure. Fly ash, a byproduct of thermal power plants, is utilized as a partial cement replacement to improve workability, durability, and environmental sustainability, while steel fibers enhance tensile strength and crack resistance. The review consolidates findings from various studies on the mechanical performance, durability characteristics, and microstructural changes of such concrete composites. Emphasis is placed on the influence of alkaline conditions, which simulate aggressive environments such as marine or industrial settings. Results indicate that optimal blending of fly ash and steel fibers can significantly improve concrete performance while reducing its environmental footprint. This review aims to support sustainable construction practices by promoting the reuse of industrial waste in high-performance concrete applications.
Keywords: Industrial Waste; Concrete Strength; Durability; Fiber Reinforced Concrete; Pozzolanic Materials; Mechanical Properties